P119 Hereditary Colorectal Cancer Syndromes and Inflammatory Bowel Diseases: an ECCO CONFER Multicenter Case Series. (21st January 2022) - Barberio, B; Savarino, E; Verstockt, B; Fumery, M; Pugliese, D; Bertani, L; Buda, A; Dragoni, G; Goren, I; Laish, I; Spinelli, A; Teich, N; et al.
Abstract: Background: Hereditary colorectal cancer syndromes (HCCS) are rare polyposis or nonpolyposis syndromes with a higher risk of developing colorectal cancer (CRC). Coexisting inflammatory bowel disease (IBD), including ulcerative colitis (UC) and Crohn's disease (CD), with HCCS is exceedingly rare and presumably increases the risk of early-onset colorectal cancer. Methods: This was a multicenter case series performed as a part of the European Crohn's and Colitis Organisation (ECCO) Collaborative Network of Exceptionally Rare case reports (CONFER) project. Results: This report includes 26 patients with IBD (10 UC, 15 CD, and one with IBD unclassified (IBD-U)) and concomitant HCCS. Among these 26 patients (median age 33 years, IQR 20–44), 15 (57.7%) were males, 24 (92.3%) Caucasians and 2 (7.7%) of Arab origin. Among patients with UC, 4 (40%) had proctitis, 3 (30%) left-sided colitis and 3 (30%) an extensive disease; while, among patients with CD, 8 (53.3%) had ileal, 5 (33.3%) ileocolonic, 2 (13.3%) colonic disease. One of these patients had ileocolonic disease associated with upper disease location and six (40%) had an associated perianal disease. Many of patients with CD had a non-stricturing non-penetrating phenotype (53.3%, n=8), while 20.0% (n=3) and 26.7% (n=4) had a stricturing or penetrating phenotype, respectively. HCCS was diagnosed before the IBD diagnosis in 11 patients (42.3%), after diagnosis of IBD in 11 patients (42.3%) and concurrently in 4 patients (15.4%). Sixteen patients had Lynch syndrome, 7 had FAP, 2 had AFAP and one had MAP. The most frequent genetic mutations were those of APC (n=7) and MLH1 (n= 7). Thirteen patients were treated with immunomodulatory (IMM) therapy. During IMM therapy, only 5 patients developed drug-induced side-effects which did not require drug interruption. One patient treated with vedolizumab developed CRC, despite yearly colonoscopy surveillance, after 4 years of treatment. Overall, CRC developed in 38.5% of patients (n=10): in 5 patients (50%) after IBD diagnosis, in 4 (40%) patients before IBD diagnosis, and in 1 patient the 2 conditions were diagnosed simultaneously. Eighteen (69.2%) patients underwent colectomy or abdominal surgery: 9 patients due to CRC diagnosis, 7 patients preventively due to the underlying HCCS and 2 patients because of active IBD disease. On follow-up, one patient died due to CRC. Conclusion: This case series describes the largest series to date of patients with IBD patients and HCCS, with special emphasis on the use of IMM in this population. The most frequent diagnosis of HCCS associated with IBD was Lynch syndrome. These data demonstrate the high malignancy rate and surgical intervention rate in this IBD cohort. The optimal medical approach still needs to be addressed.